The role of protein phosphorylation modifications mediated by iron metabolism regulatory networks in the pathogenesis of Alzheimer’s disease - Liu, Fei-Xiang; Yang, Shun-Zhi; Shi, Kai-Kai; Li, Ding-Ming; Song, Jia-bin; Sun, Lu; Dang, Xue; Li, Jin-Yao; Deng, Zi-qi; Zhao, Min; Feng, Yan-Chen (Frontiers in Aging Neuroscience, 2025)
Alzheimer’s disease (AD) is a severe neurodegenerative disease characterized mainly by the formation of amyloid beta (Aβ) plaques and abnormal phosphorylation of tau. In recent years, an imbalance in iron homeostasis has been recognized to play a key role in the pathological process of AD. Abnormal iron accumulation can activate various kinases such as glycogen synthase kinase-3β, cyclin-dependent kinase 5, and mitogen-activated protein kinase, leading to abnormal phosphorylation of tau and amyloid precursor protein, and accelerating the formation of Aβ plaques and neurofibrillary tangles. In addition, iron-mediated oxidative stress not only triggers neuronal damage, but also exacerbates neuronal dysfunction by altering the phosphorylation of N-methyl-D-aspartate receptors and γ-aminobutyric acid type A receptors. Iron accumulation also affects the phosphorylation status of tyrosine hydroxylase, the rate-limiting enzyme for dopamine synthesis, interfering with the dopamine signaling pathway. On the other hand, iron affects iron transport and metabolism in the brain by regulating the phosphorylation of transferrin, further disrupting iron homeostasis. Therapeutic strategies targeting iron metabolism show promise by reducing iron accumulation, inhibiting oxidative stress, and reducing abnormal phosphorylation of key proteins. This article reviews the molecular mechanisms of phosphorylation modifications mediated by iron homeostasis imbalance in AD, and discusses the potential of interventions that regulate iron metabolism and related signaling pathways, providing a new theoretical basis for the treatment of AD.